Cold pursuit [videorecording (DVD)] - Neeson, Liam; Bateman, Tom, 1989-; Jackson, Tom, 1948-; Rossum, Emmy, 1986- (Summit Entertainment, 2019)
Nels Coxman is a family man whose quiet life with his wife is upended following the mysterious death of their son. Nels's search for justice turns into a vengeful hunt for Viking, a drug lord he believes is connected to the death. As one by one Viking's associates 'disappear,' Nels goes from upstanding citizen to ice-cold vigilante, letting nothing, and no one, get in his way.